Kesadaran Kesehatan, Sikap, dan Perilaku Gizi Seimbang Selama Pandemi Covid-19 di Yogyakarta - Nai, Hildagardis Meliyani Erista (Jurnal Kesehatan, 2024)
The impact of COVID-19 has changed many aspects of people's lives, including health, the economy, and society. Applying balanced nutrition and healthy eating habits requires everyone's health awareness and attitude to maintain their health during a pandemic. This study aims to analyze the relationship between health awareness and attitude with balanced nutrition bahaviour during the COVID-19 pandemic in Yogyakarta City. This type of research is an analytic observational study with a cross-sectional design. The research was conducted in Yogyakarta City. The population was 121,281 people aged 20-54 years. The sample size of this study was 357 people. The sampling technique used multistage sampling by combining three sampling techniques: cluster random sampling, stratified random sampling, and simple random sampling. Data collection techniques using direct interviews with questionnaires. Data analysis used the correlation Spearman test and Mann-Whitney test. There was a significant relationship between health awareness and attitude with balanced nutrition behavior  (p<0.05); it means that the higher health awareness and attitudes related to COVID-19, the higher the balanced nutrition behavior. There needs to be an effective intervention to continue to foster health awareness and attitudes during the COVID-19 pandemic for the people of Yogyakarta City so that they are consistent in implementing balanced nutrition behavior.